Synthesis, characterization, spectral studies, and antifungal activity of Mn(II), Fe(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes with monosodium 4-(2-pyridylazo)resorcinol - Pandey G.; Narang K.K. (My University, 2025)
Mn(II), Fe(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes of the type Na2[ML2]·2H2O of the title ligand, monosodium 4-(2-pyridylazo)-resorcinol, NaHL, have been synthesized and characterized by various physico-chemical (elemental analyses, solubility, electrolytic conductances, and magnetic susceptibility measurements) and spectral (UV-Visible, IR, ESR, and powder x-ray diffraction) techniques for structure determination and tested for their antifungal activity. The 1:2 (M:L) complexes showed octahedral geometry around M(II), significant antifungal activity against Curvularia species and Collectotrichum capsici and moderate activity against the fungi Alternaria brassicicola, Alternaria brassicae, Alternaria solanae, Curvularia lunata, Helminthosporium oryzae, Aspergillus niger, Aspergillus flavus, and Fusarium udum.